Education and traning on making lipbalm as safe cosmetic in MAN 1 Kota Jambi - Pratiwi, Puspa Dwi; Yuliawati; Maharini, Indri; Syamsurizal; Maimum; Pondawinata, Marizki; Fitrianingsih (Proceedings Academic Universitas Jambi, 2025)
Background: Cosmetic products, especially lip balms, are widely used among teenagers, yet many students are unaware of the composition, safety, and proper formulation of such products. Educational activities on cosmetic formulation can enhance students’ scientific understanding and entrepreneurial potential in the cosmetic field. Objective: This community service program aimed to provide education and hands-on training to students of MAN 1 Kota Jambi on the formulation and production of lip balm cosmetics using safe and natural ingredients. Methods: The program was conducted through interactive lectures, demonstrations, and practical workshops. Participants were introduced to the basic concepts of cosmetic formulation and the role of each ingredient. The training involved direct formulation practice, including measuring, mixing, and molding lip balm preparations. Evaluation was carried out through participant satisfaction. Results: The program successfully increased students’ understanding of cosmetic formulation and safety. Participants were enthusiastic and able to produce lip balm products with proper formulation techniques. The activity also fostered creativity and entrepreneurship awareness among students. Conclusion: The education and training program effectively enhanced students’ knowledge and skills in making lip balm cosmetics. It demonstrated that practical cosmetic education can serve as an innovative approach to developing scientific literacy, creativity, and entrepreneurial spirit in students.